Bending of the rigidly fixed elastic-plastic plate - Assetova, L.S.; Nurlanova, B.M.; Samoilova, I.A. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The number of plate structures include coatings, as well as box systems, working as a complete spatial system. The plate structures include systems elements of which are both rods and plates, for example, frame-panel structures with the bearing capacity of frame-panel buildings when considering the theory of bending. In the theory of elastic-plastic plates, the algorithm of calculation according to this theory, its basic formulas, the basic relations of the theory of elasticity are considered. This article discusses the bending of the rigidly fixed elastic-plastic plate. Calculations were made using the method of separation of variables. This method was implemented in the program MathCAD. Values of the laws of stress and modulus of materials, bending functions, shear components, deformation components, bending moment values, torsion and internal forces, stresses are obtained and plots of distribution functions are plotted. The values of the distribution functions of the rigidly fixed elastic-plastic plate are determined.
Жақтары қатты бекiтiлген серпiмдi-иiлiмдi пластинаның иiлуi
Изгиб жестко закрепленной упруго-пластической пластины
Keywords: plate; elastic; plastic; malleability; bending; deformation; stress